Adaptive immune changes in colorectal cancer: a focus on T and B cell activation genes - Mona Rady; Albert Ashraf; Hesham Abdelaziz; Mohamed El-Azizi (Discover Oncology)
Abstract Colorectal cancer (CRC) ranks as the third most common cancer globally and is the second leading cause of cancer-related deaths, following lung cancer. Despite the immune system’s capacity for tumor surveillance and elimination, CRC tumors can evade immune responses through complex mechanisms, ultimately escaping immune detection. T and B lymphocytes play a critical role in adaptive immunity against tumors, with T cells, particularly CD8+ cytotoxic T cells, driving tumor elimination. Additionally, B cells contribute by producing tumor-specific antibodies, including various immunoglobulin G (IgG) subclasses that participate in immune modulation. However, the effectiveness of adaptive immunity in CRC is often limited due to tumor-driven immunosuppression. This study investigates the expression of T and B cell activation genes in peripheral blood mononuclear cells (PBMCs) isolated from CRC patients. A panel of 84 genes involved in T and B cell activation was analyzed to assess changes in expression using RT2 QPCR arrays. Additionally, we measured serum levels of the four IgG subclasses (IgG1, IgG2, IgG3, and IgG4) in CRC patients to explore possible alterations in humoral immunity. Compared to healthy controls, 5 genes were found to be downregulated in PBMCs of all CRC patients’ groups; CCL3 (fold regulation − 6.36), IL6 (fold regulation − 12.46), CSF2 (fold regulation − 7.50), CXCR3 (fold regulation − 3.01), and TNFSF14 (fold regulation − 4.90). Moreover, 13 genes were upregulated in PBMCs of all CRC patients’ groups; CCR3 (fold regulation 59.21), CD2 (fold regulation 3.07), CD27 (fold regulation 6.39), CD3G (fold regulation 4.15), CD8B (fold regulation 3.25), FAS (fold regulation 3.94), IL10 (fold regulation 39), IL18R1 (fold regulation 82.39), IL5 (fold regulation 20.4), LAG3 (fold regulation 19.88), MAP3K7 (fold regulation 4.07), TLR1 (fold regulation 6.45), and TLR6 (fold regulation 18.87). The serum levels of the four IgG subclasses were however statistically insignificant in CRC patients compared to healthy controls. Our findings provide insights into the adaptive immune dysfunction in CRC, offering a detailed profile of gene expression changes associated with T and B cell activation and antibody production. Understanding these dysregulations may enhance the development of targeted immunotherapies, potentially improving outcomes for CRC patients through more personalized immunomodulatory approaches.